2010
DOI: 10.1161/hypertensionaha.110.152868
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bed Rest on Conduit Artery Remodeling

Abstract: Abstract-Physical inactivity is a potent stimulus for vascular remodeling, leading to a marked decrease in conduit artery diameter. However, little is known about the impact of physical inactivity on artery wall thickness or wall:lumen ratio or the potential of exercise countermeasures to modify artery wall thickness. The purpose of the study was to examine the impact of 60 days of bed rest, with or without exercise countermeasures, on carotid and superficial femoral artery wall thickness. Eighteen men were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 56 publications
(60 reference statements)
7
47
3
1
Order By: Relevance
“…It is possible that the women in the present study were not as physically active prior to HDBR as the men so there was less difference between pre-and post-HDBR values, but technical difficulties reduced the sample size to 5 so the negative findings in the women should be viewed with caution. In the present study, the EX group showed no differences in pre-and post-HDBR baseline diameter values, suggesting that the exercise countermeasures, which included treadmill running, were sufficient to maintain vascular properties, while resistance or vibration exercise in men was not sufficient to maintain femoral artery diameter (40).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…It is possible that the women in the present study were not as physically active prior to HDBR as the men so there was less difference between pre-and post-HDBR values, but technical difficulties reduced the sample size to 5 so the negative findings in the women should be viewed with caution. In the present study, the EX group showed no differences in pre-and post-HDBR baseline diameter values, suggesting that the exercise countermeasures, which included treadmill running, were sufficient to maintain vascular properties, while resistance or vibration exercise in men was not sufficient to maintain femoral artery diameter (40).…”
Section: Discussioncontrasting
confidence: 45%
“…Also, there were no changes in the response to sublingual NG in either the CON or the EX groups with HDBR. Previous research with men found reduction in leg artery diameter after 52 days horizontal bed rest (5) and after 60 days HDBR with or without resistance or vibration exercise countermeasures (40). It is possible that the women in the present study were not as physically active prior to HDBR as the men so there was less difference between pre-and post-HDBR values, but technical difficulties reduced the sample size to 5 so the negative findings in the women should be viewed with caution.…”
Section: Discussionmentioning
confidence: 97%
“…In such populations vascular health is reduced and appears to deteriorate over time since the positive benefits of physical activity and the associated shear stress are absent (17,38). Hellsten et al (15) and Hoier et al (16) have documented that acute and chronic passive exercise training in healthy able-bodied individuals resulted in an angiogenic stimulus characterized by enhanced vascular endothelial growth factor, endothelial cell proliferation, and capillary growth.…”
Section: Clinical Implications For the Application Of Passive Movementmentioning
confidence: 99%
“…Our current data demonstrate that artery wall thickness should be regarded as a dynamic part of the vascular system that is able to change acutely and over the short term. 3 A plausible explanation for the changes in wall thickness to GTN relates to the conservation of arterial wall mass. The strong correlation of the arterial wall cross-sectional area before and after GTN supports this hypothesis.…”
Section: Thijssen Et Al Vascular Tone and Wall Thickness 243mentioning
confidence: 99%
“…[1][2][3][4] Conduit arterial wall thickening, particularly of the carotid artery, is regarded as a surrogate marker of the atherosclerotic process and has been used in intervention trials as a primary outcome measure. 4 -8 Noninvasive ultrasound is widely used to assess wall thickness, sometimes referred to as intima-medial thickness (IMT), which is an established independent predictor for future cardiovascular events.…”
mentioning
confidence: 99%